Anterior Clinoidal Meningiomas: Meningeal Anatomical Considerations and Surgical Implications - Xu, Tao; Yan, Yong; Evins, Alexander I.; Gong, Zhenyu; Jiang, Lei; Sun, Huaiyu; Cai, Li; Wang, Hongxiang; Li, Weiqing; Lu, Yicheng; Zhang, Ming; Chen, Juxiang (Frontiers in Oncology, 2020)
OBJECT: Surgical removal of anterior clinoidal meningiomas (ACMs) remains a challenge because of its complicated relationship with surrounding meninges, major arteries and cranial nerves. This study aims to define the meningeal structures around the anterior clinoid process (ACP) and its surgical implications. METHODS: Five dry skulls and nineteen cadavers were used anatomical study. Cadavers were prepared as transverse, coronal and sagittal plastinated sections, and the meningeal architecture around the ACP was studied with dissecting microscopy and confocal microscopy. The database of meningiomas in one single center was retrospectively reviewed, and the patients with ACMs were collected for clinical analysis. RESULTS：The superior, lateral, medial surfaces and the tip of ACP were covered by different layers and types of meninges. The ACMs were classified into four main types based on the sites of origin, possible extending pathways following meningeal dura. In the retrospective cohort of 131 ACMs, the percentage of types I, IIa, IIb, III, and IV were 42.0% (55/131), 19.8% (26/131), 9.2% (12/131), 16.8% (22/131) and 12.2% (16/131), respectively. We found Type IIa and Type I had higher chances for achieving Simpson grade 1-2 resection (92.3% and 85.4%, respectively), followed by Type III (54.5%), and Type IV (31.3%), while Type IIb showed little chance of Simpson grade 1-2 resection. Univariate and multivariate analysis revealed ACMs classification, tumor size (>3cm) to be independent risk factors for achieving more extensive resection. CONCLUSION: The meningeal architecture around the ACP may guide and determine the origin and extension of ACMs. The classification based on the meningeal architecture helps to understand surgical anatomy as well as predicting surgical outcomes.